1986
DOI: 10.1111/j.1365-2222.1986.tb00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of skin test and RAST in allergy to a clinically potent allergen (castor bean)

Abstract: Summary In order to investigate once more the usefulness of the RAST procedure in the diagnosis of reaginic hypersensitivity, we studied a series of patients showing a well known sensitivity to castor bean, which is a potent antigen, and compared the results with those given by patients with no clinical allergy to this antigen as confirmed by negative skin testing. The latter group included patients with no contact, a remote contact or a close contact with castor bean. Castor bean allergy seems to be a good mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Several studies were found to investigate the allergenic properties of castor beans, from which castor oil is extracted. Individuals have reported asthma after exposure to castor beans (Panzani and Johansson, 1986). Castor oil might cause contact dermatitis (Di Berardino and Della Torre, 2003).…”
Section: Allergymentioning
confidence: 99%
“…Several studies were found to investigate the allergenic properties of castor beans, from which castor oil is extracted. Individuals have reported asthma after exposure to castor beans (Panzani and Johansson, 1986). Castor oil might cause contact dermatitis (Di Berardino and Della Torre, 2003).…”
Section: Allergymentioning
confidence: 99%
“…This high level of reliability, coupled with the low risk of an in vitro test, has made IgEQAA a useful tool in the treatment of allergic diseases. 4 AD has been shown to be aggravated by multiple different environmental allergens, especially certain aeroallergens. In a study conducted by Goon et al, it has been shown that patients with AD tested positive to both atopic patch and IgEQAA testing for house dust mites at a level significantly higher than that of controls.…”
Section: Introductionmentioning
confidence: 99%
“…This method is more sensitive and specific than the in vitro test, the radioallergosorbent test (RAST) technique, which measures specific IgE antibody in the blood against a particular allergen. 14 The level of antibody correlates approximately with the degree of allergen sensitivity to that allergen.…”
Section: Laboratory Evaluationmentioning
confidence: 99%